Physical and statistical analysis procedure of solar irradiance measurements based on sky cover conditions - Contes Calca, Marcus V. [UNESP]; Raniero, Matheus Rodrigues [UNESP]; Campos, Firmo Sousa [UNESP]; Zeca Fernandes, Domingos M.; Rodrigues, Sergio Augusto [UNESP]; Pai, Alexandre Dal [UNESP] (International Solar Energy Society (ISES), 2020)
The correct quality assessment of solar irradiance data allows public bodies, academic entities and nongovernmental organizations to plan and manage renewable energy resources more appropriately in Brazil. This study presents a physical and statistical analysis procedure used by the Solar Radiometry Laboratory of the School of Agricultural Sciences (São Paulo State University - UNESP), in Botucatu/São Paulo/Brazil, to check the reliability of 5-minute instantaneous average measurements (Wm-2) of global (IG), sky-diffuse (ID) and direct-beam (IB) solar irradiances in horizontal surfaces. The procedure was implemented based on quality control of the International Commission on Illumination (CIE) to detect physically impossible events (absolute and consistency checks) and statistical ranges in function of sky cover conditions to identify uncertain events. A set of measurements (2005 to 2007) was used to demonstrate the application of this procedure. It was found by the physical analysis that the absolute check identified the least amount and the consistency check the largest amount of physically impossible and discrepant quantities measurement values, as well as the statistical ranges allowed to identify data points not signaled by the previous criteria, pointing uncertain solar irradiance observations (outliers). The procedure application indicated that 94.77% of global, 97.12% of sky-diffuse and 98.16% of direct-beam irradiances were flagged as validated, indicating a high quality of measurements, that can be used to assist Brazilian organizations in the planning of renewable energy systems.
Keywords: Quality assessment of solar measurements; Sky coverage; Solar radiation; Statistical ranges